Strategi Pengembangan Industri Kreatif Kerajinan Rajapolah Melalui Pendekatan Resource Based View (RBV) - Arif; Gian Riksa Wibawa (Universitas Medan Area, 2022)
UMKM Rajapolah is one of the areas in Tasikmalaya which produces handicrafts from mendong, pandanus and water hyacinth plants. Products from this handicraft have long been in demand by various groups of local tourists and have succeeded in penetrating the international market. The number of business actors engaged in the industry is currently 939 MSMEs. This study aims to identify resources and capabilities through value chain activities in creating sustainable competitive advantage in the Rajapolah handicraft industry. The research method used in this study is qualitative. Data collection was carried out by means of semi-structured interviews which were freer in finding research problems and distributing questionnaires. The sampling method used is the snowball technique by producing 5 respondents. The results of the study state that the external analysis of Porter's Five Forces shows that the attractiveness of the Rajapolah craft industry is less attractive. The level of sales of Rajapolah handicrafts has not returned to normal since the pandemic emerged, this is supported by the fact that 63% of MSMEs have difficulty running company operations. Based on the internal analysis of the value chain produces 9 resources and 13 capabilities in increasing customer value.